The effect of board thickness on the stiffness of the profiled steel sheeting dry board (pssdb) floor panel - Nur Afifah , Zainuddin (2014)
The past decade has seen an increasingly rapid development in the field of construction due to an initiative from the government to boot the economy and enhance the standard of living. However, these rapid changes result in many delayed and non-completion projects. Due to these matters, there is an extremely hih number of lost and cost in terms of wastage and pollution. One effective solution Is to implement the Industrialized Building System (IBS) such as the Profiled Steel Sheeting Diy Board (PSSDB). PSSDB is a composite structural panel consists of three elements which are the dry board, steel sheeting and self tapping screw as connection. It can be used as a wall, roof or floor panel. This research studies the effect of dry -board thickness on the overall-floor panel stifThess. -Two -different thicknesses of Primaflex dry board; 6 mm and 9 mm, were used whilst the Peva 45 profiled steel sheeting thickness was maintained at 0.8 mm. Bending tests were performed to identify the thickness that contributed to the higher stiffness of the floor panel. From the result, the maximum load for 6 mm and 9 mm boards are 24.51 kN/m2 and 27.2 kN/m 2 respectively. The stiffness of the panels was also determined from the slope of the load versus the deflection graph. The stiffness value for the 6 mm board is 85 kNm 2 /m. In comparison, the stifffiess value of 9 mm Primaflex dry board is 89 kNm 2 /m. It can be concluded that the thicker the dry board, the stiffer the floor panel will be. The Primaflex dry board has shown to have a better bending flexibility and a potentially suitable dryboard choice in PSSDB.